A new genus of soft coral (Octocorallia: Alcyonacea: Clavulariidae) from Chile - van Ofwegen, L. P.; Häussermann, V.; Försterra, G. (Zootaxa, 2006)
Incrustatus comauensis n. gen. & n. sp. (Octocorallia: Clavulariidae) is described from Chile. It occurs in shallow water from Concepción to the southern fjord region. The genus forms stolons on mytilid shells and rocks, or encrusting sheets on Crepidula shells (Gastropoda), polychaete tubes, gorgonians, and other substrata. The sclerites of the new taxon are 8-radiates and derivatives of these. The polyps are unarmed or posses a few irregularly arranged spindles. The new genus is compared with another taxon that forms encrusting sheets or stolons.